Weighted aspirations: becoming a teenage dropout in El Salvador - Mordy, Meghan Katherine, author; Peek, Lori, advisor; Hempel, Lynn, committee member; Taylor, Peter L., committee member; Velasco, Marcela, committee member (Colorado State University. Libraries, 2020)
The vast majority of poor and low-income students in El Salvador drop out during middle school or early high school. This dissertation is dedicated to describing their experiences and understanding the reasons why so many of them abandon their education as teenagers. Because of the high rates of urban violence in the nation, it focuses specifically on urban youth. The findings are based on three years of qualitative fieldwork in two urban schools—La Laguna and Cerro Verde—in a densely populated city in the metropolitan region near San Salvador. I conducted over 200 days of ethnographic observations, student focus groups, teacher interviews, and a student survey at the schools. In addition, I interviewed in-depth 54 dropouts, 28 high school graduates, and 19 mothers or grandmothers. This dissertation has shown the roots of dropout as deeply entangled in family poverty, community instability, and school failure. The students at La Laguna and Cerro Verde came from very poor backgrounds, but, despite their daily hardships, they and their families had faith in education and very high aspirations to graduate high school. Most wanted to go to college and believed strongly they would achieve their dreams. The contexts of their lives, however, weighed heavily against these aspirations. The lack of living-wage jobs meant parents had very low or unstable incomes and few material resources to invest in their children's education. The informal or blue collar work that parents did was also so stressful, tiresome, and physically degrading that it took a toll on parent-child relationships, adults' relationships with one another, and health and wellbeing. Family economies were highly vulnerable to shocks. A parents' illness, a broken marriage, or a loan coming due could deeply disrupt their ability to put food on the table. When youth saw their parents showing signs of distress many felt compelled to help out by working. Youth knew the outsized value their poor families could derive from even meager earnings and dropped of school to become wage earners of last resort. Household and community violence intensified the insecurity in poor youth's lives. Children living in violent households suffered physically, emotionally, and educationally. Families living in violent neighborhoods limited their children's contact with neighbors and friends. But some families experienced violence directly. Homicide, assault, threats, and police brutality devastated them, causing significant emotional and economic harm. Youth left school behind to help their families cope through what were sometimes extended crises stemming from the violence swirling all around. Schools in El Salvador have been idealized as an ameliorative for these worst aspects of poverty and tasked with the mission of providing poor children the knowledge and skills they need for gainful employment. But the situation at La Laguna and Cerro Verde showed the faulty foundations of this ideal. These schools lacked critical infrastructure, textbooks, and learning materials. Their overworked and under-trained teachers relied on outdated teaching methods and had no support systems for addressing students' remedial issues or emotional and behavioral problems. As a result, students received very little quality instruction and learned much less than they should. A legacy of learning deficits trailed them as they passed from grade to grade. By middle school, many students lacked the basic skills they need to keep up with the curriculum. Low grades and frustration eroded their motivation to make an effort in the classroom. Some students became deeply disillusioned and frustrated with their lack of comprehension and dropped out of school to avoid these emotions. Others noted they could not pass and left before being flunked. A hostile school climate worsened conditions. Students could feel rebuffed and alienated by their teachers' harsh talk and authoritarian approaches to discipline. Classmates often treated each other aggressively and fights were common. A significant number of students were threatened, harassed, or bullied by peers. Some youth experienced conflicts with teachers or peers over extended periods and, perceiving the abuse would continue or more harm could come to them, opted to drop out. In the end, the students' and their families' commitment to schooling was undermined by the compounding hazards of poverty. Families, schools, and communities did not have the resources needed to sustain these young people's aspirations. This dissertation brings to life their voices and stories, displaying how a vicious circle of deeply structured inequalities batters against the dreams of poor and vulnerable children.
Keywords: dropout; qualitative methods; sociology of development; educational attainment; Central America